Identification key to nymphal and adult mealybugs (Hemiptera: Pseudococcidae) associated with dragon fruits in Indonesia - Mila Seri Rezeki; IDHAM SAKTI HARAHAP; DEWI SARTIAMI; IRMANSYAH IRMANSYAH; GILLIAN W. WATSON (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rezeki MS, Harahap IS, Sartiami D, Irmansyah, Watson GW. 2021. Identification key to nymphal and adult mealybugs (Hemiptera: Pseudococcidae) associated with dragon fruits in Indonesia. Biodiversitas 22: 3113-3118. Dragon fruit (Hylocereus spp.), belonging to Cactaceae family, is one of the horticultural commodities being developed in Indonesia for export. Phytosanitary regulations require that fruits for export must be free from diseases and pests, including mealybugs (Hemiptera: Pseudococcidae). Mealybug species commonly found on dragon fruits in Indonesia are Ferrisia virgata (Cockerell), Phenacoccus solenopsis Tinsley, Planococcus minor (Maskell) and Pseudococcus jackbeardsleyi Gimpel & Miller. Species-level identification of these insects in the nymphal phase is difficult due to the limited number of identification keys available, so it has been necessary to create an identification key to nymphs of mealybug species found on dragon fruit. A dichotomous identification key was constructed based on microscopic morphological characteristics of the cuticle. Thus, the four species can be differentiated based on general and unique characteristics of each species in the nymphal and adult stages. The diagnostic features that can be used to separate the four species in the nymphal phase are the presence or absence of: discoidal pores around the eyes; anal lobe bars; tubular ducts on the dorsum; and a denticle on each tarsal claw.